PERANAN BEA CUKAI DALAM PENGAWASAN TERHADAP BARANG YANG MASUK MELALUI PERAIRAN ASAHAN –TANJUNG BALAI (STUDI DI KANTOR BEA DAN CUKAI KOTA TANJUNG BALAI) - Meirad Arianza Bima; Rika Rahayu; Shely Winata; Erwin Syahputra (Nusantara Hasana Berdikari, 2022)
Customs is the name of a government agency related to international trade both in its role of supervising and collecting import duties, export duties and import taxes. However, customs itself has a different definition, namely duty which is a state levy on imported and exported goods, while excise is a state levy imposed on certain goods with the characteristics of controlled circulation, controlled consumption and high value. This study examines the Guidance and Supervision of Savings and Loan Cooperatives. in this legal research using empirical legal research methods and conducting a study at the Tanjungbalai City Customs and Excise Office. In this legal research, primary legal materials are used, namely: Legislation. Secondary legal materials, namely: law books. Tertiary legal materials, namely: non-legal books. The role of the Tanjungbalai City Customs and Excise office in supervising the smuggling of excisable goods is very important because it is our duty to prevent smuggling, and we always try to prevent smuggling. to the southern stone harbor. In this case, the obstacles faced by the Customs and Excise office in supervising the smuggling of excisable goods into and out of Tanjungbalai City are that people prefer to buy excisable goods at a cheaper price. And the cheap ones are usually goods that are not subject to official excise duty or what are commonly called illegal goods. For example, cigarettes that are not subject to excise duty.